Análise da compartimentação geomorfológica do Município de Alto Alegre – Roraima - Maia, Victor Viriato (2020)
The extreme north portion of Brazil has a geomorphology of peculiar characteristics and corresponds to one of the surfaces with the highest altimetric levels in the entire Brazilian Amazon. Geomorphologically, this portion of the Brazilian territory presents a diversity of types of landscapes, and they have natural resources inside that serve as important factors in the understanding of environmental phenomena. The state of Roraima inserted in this portion, has in its landscape context a diversified arrangement of types of relief, comprising different geomorphological models. Among these, we highlight those located in the municipality of Alto Alegre, which have geomorphological potentialities and arouse curiosities in mapping their landforms more punctually. In view of these impressions, this work aimed to analyze the geomorphological compartments of the municipality of Alto Alegre - RR, using remote sensing and field data using the application of photointerpretative techniques in remote sensor images (landsat 8 OLI sensor and the Digital Elevation Model (MDE)) and geoprocessing, these in turn, have undergone a rigorous treatment process that depends on the correct application of processing operations aimed at mitigating the effects of atmospheric interference where after processing they have made geomorphological compartmentation efficient the studied region. The geomorphological mapping made it possible to identify various forms of relief, mainly of Structured Mountains, Serranias With Embedded Valley, Hills and Hills Staggered with Open Valleys, Hills on Structured Landings, Tabular Plateau, Canyons, Open Dissected Hills, Alluvial Plain (PAL), Surface Planed (SAP), among others. Therefore, the geomorphological contexts analyzed here serve as a tool for the management and zoning of the local landscape in the various forms of occupation and use of the studied area.